Effect of antenatal iodinated contrast agent on neonatal thyroid function - Rajaram, S (The British Institute of Radiology., 2012)
OBJECTIVE: The aim of this study was to assess the effect on neonatal thyroid function of iodinated contrast media administered for CT pulmonary angiography (CTPA) in babies whose mothers were investigated for suspected pulmonary embolism during pregnancy. METHODS: Retrospective review of 115 pregnant patients investigated for suspected pulmonary embolism. The patient cohort consisted of two groups: Group A consisted of 73 pregnant females who received iodinated contrast agent for CTPA, and Group B (control group) consisted of 42 pregnant females who were investigated by perfusion imaging only. The results of the neonatal thyroid function tests for the babies of the mothers in Groups A and B were compared. RESULTS: All of the neonatal thyroid function tests for both groups were normal with no statistical difference between the two groups. CONCLUSION: No adverse effect on thyroid function was demonstrated in neonates exposed to in utero iodinated contrast media. However, as our study involves a small patient group, the results should be interpreted with caution.